Genome-wide identification and functional analysis of long non-coding RNAs in Chilo suppressalis reveal their potential roles in chlorantraniliprole resistance - Huang, Shuijin; Jing, Dong; Xu, Lu; Luo, Guanghua; Hu, Yanyue; Wu, Ting; Hu, Yao; Li, Fei; He, Kang; Qin, Wenjing; Sun, Yang; Liu, Hui (Frontiers in Physiology, 2023)
Long noncoding RNAs (lncRNAs) perform essential functions in biological processes such as reproduction, metamorphosis and other critical life functions. Yet, lncRNAs are poorly understood in pesticide resistance and no reports to date have characterized which lncRNAs are associated with chlorantraniliprole resistance in Chilo suppressalis. Here, RNA-seq was performed on a susceptible strain (S) and a resistant strain (R) of C. suppressalis exposed to chlorantraniliprole. In total, 3470 lncRNAs were identified from 40,573 merged transcripts in six libraries, including 1879 lincRNAs, 245 introniclncRNAs, 853 sense lncRNAs and 493 antisense lncRNAs. Moreover, differential expression analysis revealed 297 and 335 lncRNAs up-regulated in S and R strains, respectively. Most of the differentially expressed (DE) lncRNAs were hypothesized to be associated with chlorantraniliprole resistance in C. suppressalis. As potential targets, adjacent protein coding genes (<1000 kb upstream and downstream of DE lncRNAs), especially detoxification enzyme genes (cytochrome P450s, carboxyl/cholinesterases/esterases, and ATP-binding cassette transporter) were analyzed. Furthermore, the strand-specific RT-PCR was conducted to determine the transcript orientation of randomly selected 20 DE lincRNAs and qRT-PCR was performed to verify the expression level of 8 out of them. MSTRG.25315.3, MSTRG.25315.6 and MSTRG.7482.1 were up-regulated in R strain. Lastly, RNA interference and bioassay analyses indicated overexpressed lincRNAMSTRG.7482.1 were involved in chlorantraniliprole resistance. In conclusion, we represent the first genome-wide identification of lncRNAs associated with chlorantraniliprole resistance in C. suppressalis. It expands views underlying the mechanism conferring chlorantraniliprole resistance in lncRNA.